Identification of a new pebp2alphaA2 isoform from zebrafish runx2 capable of inducing osteocalcin gene expression in vitro - Pinto, Jorge P; Conceição, Natércia M; Viegas, Carla S B; Leite, Ricardo B; Hurst, Laurence D; Kelsh, Robert N; Cancela, M Leonor (Journal of bone and mineral research, 2005)
The zebrafish runx2b transcription factor is an ortholog of RUNX2 and is highly conserved at the structural level. The runx2b pebp2alphaA2 isoform induces osteocalcin gene expression by binding to a specific region of the promoter and seems to have been selectively conserved in the teleost lineage. RUNX2 (also known as CBFA1/Osf2/AML3/PEBP2alphaA) is a transcription factor essential for bone formation in mammals, as well as for osteoblast and chondrocyte differentiation, through regulation of expression of several bone- and cartilage-related genes. Since its discovery, Runx2 has been the subject of intense studies, mainly focused in unveiling regulatory targets of this transcription factor in high vertebrates. However, no single study has been published addressing the role of Runx2 in bone metabolism of low vertebrates. While analyzing the zebrafish (Danio rerio) runx2 gene, we identified the presence of two orthologs of RUNX2, which we named runx2a and runx2b and cloned a pebp2alphaA-like transcript of the runx2b gene, which we named pebp2alphaA2. Zebrafish runx2b gene and cDNA were isolated by RT-PCR and sequence data mining. The 3D structure of runx2b runt domain was modeled using mouse Runx1 runt as template. The regulatory effect of pebp2alphaA2 on osteocalcin expression was analyzed by transient co-transfection experiments using a luciferase reporter gene. Phylogenetic analysis of available Runx sequences was performed with TREE_PUZZLE 5.2. and MrBayes. We showed that the runx2b gene structure is highly conserved between mammals and fish. Zebrafish runx2b has two promoter regions separated by a large intron. Sequence analysis suggested that the runx2b gene encodes three distinct isoforms, by a combination of alternative splicing and differential promoter activation, as described for the human gene. We have cloned a pebp2alphaA-like transcript of the runx2b gene, which we named pebp2alphaA2, and showed its high degree of sequence similarity with the mammalian pebp2alphaA. The cloned zebrafish osteocalcin promoter was found to contain three putative runx2-binding elements, and one of them, located at -221 from the ATG, was capable of mediating pebp2alphaA2 transactivation. In addition, cross-species transactivation was also confirmed because the mouse Cbfa1 was able to induce the zebrafish osteocalcin promoter, whereas the zebrafish pebp2alphaA2 activated the murine osteocalcin promoter. These results are consistent with the high degree of evolutionary conservation of these proteins. The 3D structure of the runx2b runt domain was modeled based on the runt domain of mouse Runx1. Results show a high degree of similarity in the 3D configuration of the DNA binding regions from both domains, with significant differences only observed in non-DNA binding regions or in DNA-binding regions known to accommodate considerable structure flexibility. Phylogenetic analysis was used to clarify the relationship between the isoforms of each of the two zebrafish Runx2 orthologs and other Runx proteins. Both zebrafish runx2 genes clustered with other Runx2 sequences. The duplication event seemed, however, to be so old that, whereas Runx2b clearly clusters with the other fish sequences, it is unclear whether Runx2a clusters with Runx2 from higher vertebrates or from other fish.